Pendampingan Dukungan Psikososial pada Klien dengan Penyakit Tidak Menular di Wilayah Cilandak Jakarta Selatan - Dinarti Dinarti; Heni Nurhaeni (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The family is an environment where several people who live together have blood relations, there are ties, obligations, shared responsibilities between those people/individuals. The family is a modern environment that must find its place in a dynamically changing and functioning society. The purpose of this community service activity is the result of research on psychosocial assistance during the pandemic in DKI Jakarta, which is to show the effectiveness of model family assistance on independent psychosocial interventions in the family. The mentoring method uses the results of development analysis with the role of effective mentoring for Health Cadres, Mothers around the Cilandak area, South Jakarta. The results of the assistance found that the importance of the function of family rights for members and all communities as well as identifying risks and forms of social and family support and policies. However, a number of findings indicate that it is impossible for every family to carry out its functions independently. Where the types of psychosocial stressors can come from marriage, parental problems, interpersonal relationships, environment, work, finances, law, developmental tasks, physical illness/injury, family factors, and others. 85% satisfaction of psychosocial assistance intervention was found to experience a decrease in stress to stress adaptation from 38 cases to 14 cases at the end of the first semester, and only 2 cases at the end of the semester. Therefore, MAPAM as a model of psychosocial assistance can be recommended to be used when carrying out assistance to the community.